Cross-sectional and prospective relations between dysfunctional cognitive beliefs and obsessive-compulsive symptoms during late childhood and early adolescence: a test of two aetiological models - Barcaccia, Barbara; Cervin, Matti; Borrelli, Davide Fausto; Mignarri, Giulia; Mancini, Francesco; Pozza, Andrea (Journal of Child Psychology and Psychiatry, 2025)
Background Obsessive-compulsive symptoms (OCS) often emerge during childhood and adolescence, and two aetiological models have been proposed. According to the first model, maladaptive cognitive beliefs facilitate the transformation of transient intrusive thoughts into OCS. The second model suggests that dysfunctional cognitive beliefs develop in response to increased levels of OCS. Few studies have contrasted these models, and no study has used a prospective design. Methods In this study, dysfunctional cognitive beliefs, OCS, depressive symptoms, and anxiety symptoms were measured repeatedly on three occasions during a year in a sample of 950 late-childhood children and early adolescents (Mage = 10.80 [SD = 1.23], 51% female). Network analysis was used to examine cross-sectional between-person associations, and a random-intercept cross-lagged panel model was used to examine prospective within-person associations. Results Cross-sectional network analyses indicated that dysfunctional cognitive beliefs were uniquely linked to OCS and significantly more strongly linked to these symptoms than to depression and anxiety. Prospective data did not support either model, but OCS and anxiety symptoms uniquely predicted each other. Sex-stratified analyses showed that dysfunctional cognitive beliefs predicted all types of symptoms at later time points in boys, while in girls, OCS and anxiety symptoms predicted each other. Assumptions of the two aetiological models of OCD were supported by cross-sectional but not prospective data. Conclusions During late childhood and early adolescence dysfunctional cognitive beliefs may play a more prominent role in the emergence of mental health symptoms in boys than in girls, but more prospective studies are needed.